Utilization of Accreditation Results to Improve the Quality of Education at Muhammadiyah Schools in Medan City - Irfan (Jurnal Inovasi dan Pengabdian, 2026)
This study aims to analyze the utilization of accreditation results by Muhammadiyah schools in Medan City to improve educational quality. Accreditation is an important instrument for evaluating educational standards, encompassing the eight National Education Standards (SNP) and providing recommendations for improvement. The research method used was descriptive qualitative, with data collected through interviews, observation, and documentation at several Muhammadiyah schools in Medan. The research focused on how the findings and recommendations from the accreditation assessor team were integrated into school program planning and implementation. The results indicate that Muhammadiyah schools in Medan City strive to utilize accreditation results as a reference in efforts to improve educational quality and school development plans. Various preparations made before and during the accreditation process (such as administrative restructuring and infrastructure improvements) directly contribute to maintaining and improving educational quality. The schools, supported by the Medan City Regional Elementary and Secondary Education Council (Dikdasmen), use the accreditation team's recommendations to provide teacher guidance, improve the learning process, and ensure compliance with standards deemed lacking. Overall, the utilization of accreditation results has a positive impact in encouraging motivation to continuously improve school quality, increasing community trust, and supporting the development of school community performance within the Muhammadiyah community in Medan City.